New cataloguing rules: steps toward a promising but uncertain future - Estivill-Rius, Assumpció (Anuario ThinkEPI, 2011)
The main features of the resource description and access (RDA) standard, published in 2010, are analyzed. Designed to facilitate the capture, storage, retrieval and visualization of data with the most advanced data base technologies, RDA remains compatible with older technology still in use. Its advantages and disadvantages, relationship to other bibliographic standards and some consequences of its implementation are discussed.